Essentials of Aquaphotomics and Its Chemometrics Approaches - Tsenkova, Roumiana; Munćan, Jelena; Pollner, Bernhard; Kovacs, Zoltan (Frontiers in Chemistry, 2018)
Aquaphotomics is a new scientific discipline involving the study of water and aqueous systems. Using light-water interaction, aquaphotomics aims to extract information about the structure of water, composed of many different water molecular conformations using their absorbance bands. Aquaphotomics aims to relate the specific water structures presented as water absorbance patterns to their resulting functions in the studied aqueous systems, thus building an aquaphotome – a database of water absorbance bands and patterns correlating specific water structures to their specific functions. Light-water interaction methods such as spectroscopy produce complex multidimensional spectral data. Extracting the hidden information about the water structure from such data requires data processing and analysis methods. The process of extracting information from the water spectra in aquaphotomics, requires field–specific approach, which starts with the appropriate experimental design and execution, ensuring high quality of spectral signal, followed by a multitude of spectral analyses, preprocessing and chemometrics methods aimed at removing unwanted influences and extracting the water absorbance spectral pattern related to the perturbation of interest through the identification of activated water absorbance bands found among the common and consistently repeating highly influential variables in all analytical models. The objective of this paper is to introduce the field of aquaphotomics and describe aquaphotomics multivariate analysis methodology developed during the last decade. Through a worked-out example of analysis of potassium chloride solutions supported by similar approaches from the existing aquaphotomics literature, the instructions provided should give enough information for anyone interested in aquaphotomics analysis about how to design and perform the experiment, how to perform each step of the analysis and finally how to represent water absorbance spectral pattern using various forms of aquagrams – specifically designed aquaphotomics graphs. The methodology explained is derived from analysis of near infrared spectral data of aqueous systems and will provide interested scientists and chemometricians a useful, new tool for extracting data from informationally rich water spectra in any region of electromagnetic spectrum. It is the hope of the authors that, with this new tool at their disposal, the pharmaceutical and biomedical spectroscopy applications will substantially progress beyond their current state of the art